2013
DOI: 10.2147/cia.s42224
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study: can older inactive adults learn how to reach the required intensity of physical activity guideline?

Abstract: Most individuals do not reach the recommended physical activity level of at least 150 minutes of aerobic exercise (AE) at moderate-to-vigorous intensity per week. For example, only 13% of older Canadian adults reach World Health Organization physical activity guideline (PAG). One of the reasons might be a difficulty identifying the required intensity. Twenty-five inactive older adults received one session about the AE-PAG and how to use a tool or strategy to help them identify AE intensity: heart-rate (HR) mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…8,12 It has been recommended that ≥100 steps minute −1 is a walking cadence consistent with moderate-intensity physical activity 13 and is appropriate for older adults. 12 The use of walking cadence as a method to monitor the intensity of physical activity among older adults is intuitive, economical, and encourages the use of pedometers, 14,15 which have been successfully used to promote physical activity in clinical practice. [16][17][18] Despite the use of walking cadence to quantify intensity of physical activity, it is unknown whether walking cadence could be additionally leveraged as an objective measure of physical function to prognosticate mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12 It has been recommended that ≥100 steps minute −1 is a walking cadence consistent with moderate-intensity physical activity 13 and is appropriate for older adults. 12 The use of walking cadence as a method to monitor the intensity of physical activity among older adults is intuitive, economical, and encourages the use of pedometers, 14,15 which have been successfully used to promote physical activity in clinical practice. [16][17][18] Despite the use of walking cadence to quantify intensity of physical activity, it is unknown whether walking cadence could be additionally leveraged as an objective measure of physical function to prognosticate mortality.…”
Section: Introductionmentioning
confidence: 99%
“…19 Establishing the relationship between walking cadence and mortality may help clinicians convey the prognostic importance of physical function to patients using a metric that is readily understood by older adults. 14 Such metrics may empower motivated older adults with the ability to self-monitor their physical function longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…This proportion is even lower from an inactive older sample (20%) previously studied by our group. 10 The biggest difference between the two samples is the fact that a large proportion of individuals who self-identify as active overestimated moderate intensity while older adults underestimated moderate intensity. 10 A previous study has suggested that regular exercisers may underestimate physical exertion when using a self-perception measure normally based on the Borg scale, 16 which helps exercisers evaluate their intensity perception on a scale between 6 and 20 or 0 and 10.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was shown that only 20% of inactive older adults could identify moderate intensity. 10 It is also important to understand if active people can identify moderate intensity because they might be the segment of the population most receptive to optimizing their aerobic exercise sessions. If active people underestimate exercise intensity (perceive the task to be moderate, but it is actually at low intensity based on the individual physiological response), they might decrease the odds of meeting their goals and expectations, therefore negatively impacting their exercise adherence and PA levels.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving the moderate-intensity in an exercise program associated with a pedometer using steps per min (cadence) seems to be a promising method. Bouchard et al [10] suggested that the use of a pedometer to estimate the exercise intensity and reported that this method should be improved to the ability to estimate the moderate intensity.…”
mentioning
confidence: 99%